Medical Equipment for Breast Clinics a View of Clinical Engineering from Practice - Martínez-Chávez G. A. (Revista Mexicana de Ingenieria Biomedica, 2019)
The present work describes the experience which involved the medical management of medical equipment for the establishment of the first and third breast cancer clinic in the Mexican Social Security Institute (IMSS) Delegation CDMX South to development a national program for detection, diagnosis and treatment of breast cancer with op-timal quality, friendliness and respect for patients’ rights. In this sense it expose the main arguments referring to the guidelines used to validate the performance of digital masthographs, are exposed for being this equipment for the most representative in the project, for which a technical information templates was developed, that applied in six mammography’s equipment which are the concepts that intervene in technical specifications analysis, empha-sizing the detectors response, dosimetry, contrast and image quality among the main aspects. With the premise of sharing the experiences obtained in the creation of these clinics, and the roll of the biomedical engineer as part multidisciplinary team, and considered optimization of knowledge manager as regarding imaging equipment in each of the medical units.